The biology of the eye - Fischbarg, Jorge (Advances in organ biology, 2006)
Explores the many novel ideas about the eye in a systematic and synthetic way. This work includes both basic sciences and applications towards clinical research. It contains chapters that include both anatomical and functional descriptions of different ocular tissues. It is suitable to students in basic biomedical science, and ophthalmologists.